2015
DOI: 10.3109/14992027.2014.986692
|View full text |Cite
|
Sign up to set email alerts
|

Modulation masking release using the Brazilian-Portuguese HINT: Psychometric functions and the effect of speech time compression

Abstract: Objective The Brazilian-Portuguese Hearing In Noise Test (HINT) was used to investigate the benefit to speech recognition of listening in a fluctuating background. The goal was to determine whether modulation masking release varied as a function of the speech-to-masker ratio at threshold. Speech-to-masker ratio at threshold was manipulated using the novel approach of adjusting the time-compression of the speech. Design Experiment 1 measured performance-intensity functions in both a steady speech-shaped noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
1
13
1
3
Order By: Relevance
“…This interaction between the speech and masker modulation rate is further supported by Grose et al (2015) who time-compressed the target talker, rather than the modulated noise. In that study they found reduced MR with 50% time compression which resulted in the primary speech fluctuations approximating the 10-Hz fluctuation rate of the masker.…”
Section: A Natural Conditionmentioning
confidence: 84%
“…This interaction between the speech and masker modulation rate is further supported by Grose et al (2015) who time-compressed the target talker, rather than the modulated noise. In that study they found reduced MR with 50% time compression which resulted in the primary speech fluctuations approximating the 10-Hz fluctuation rate of the masker.…”
Section: A Natural Conditionmentioning
confidence: 84%
“…A third aspect that has been observed in the study of MMR is speech-to-noise ratio (SNR). Several studies have shown that, for listeners with normal hearing, MMR decreases as SNR increases (11) .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, many studies have compared speech recognition in steady noise with speech recognition in modulated noise, both presented with the same speech-to-noise ratio (SNR) [1][2][3] . In normally hearing subjects, speech recognition performance is substantially better in modulated noise when compared with steady noise -a phenomenon referred to as modulation masking release (MMR) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Such increase is greater for modulated noise than steady noise. Consequently, MMR magnitude decreases as speech time-compression level increases 1,3 . MMR magnitudes in relation to the speech timecompression levels and the masking-noise modulation rates are relatively well established in the literature when assessed separeted [8][9][10] .…”
mentioning
confidence: 99%
See 1 more Smart Citation